Green building and its carbon footprint - Lee, Wei Liang. (2011)
IES (Integrated Environment Solution) VE-ware is a building simulation software that is able to generate the carbon footprint and the energy usage of a building. With reference to journals on LCA of buildings and other related journals, the operation phase of the building was identified to be the predominant period of a building‟s lifespan and this relate to the building‟s greatest environmental impact as well. This information set the direction and boundary for the study in this project. During the operation phrase of a building, four areas were identified to be the main energy consumption parameters. They are; 1. Windows to Walls ratio (WWR) 2. Green Roof 3. Phase Changing materials (PCM) 4. Orientation of building The buildings location was varied as well. Three locations; Singapore, Alaska and Spain were chosen to represent a tropical, a cold and a temperate climate respectively. The building‟s HVAC system was assigned to be: Split systems with mechanical ventilation with cooling. The control building was designed to be at 35th storey tall with a floor area of 70,875m2 .It‟s service life was assumed to be of more than 50 years as well.